Mapeamento de pesquisas sobre currículos de matemática na educação básica brasileira (1987 a 2012) - Palanch, Wagner Barbosa de Lima (2016)
The present study aims to investigate and analyze the academic production expressed in thesis and dissertations on Mathematics Curriculum produced in the 1987-2012 period within the Brazilian basic education, in order to study and understand the configuration of this issue in the field of mathematics education. As theoretical contributions we based our research on some authors such as Sacristan, Doll, Pacheco, Rico, Pires and others whose studies are dedicated to curriculum and mathematics education. Methodologically, the research is assumed as state of the art and as an investigation into the qualitative approach, having as object of study thesis and dissertations that deal with Mathematics Curriculum in the Brazilian Basic Education, specifically Primary and Secondary Education, that were available on CAPES website (summaries) and digital libraries of Brazilian graduation programs (full articles). For data analysis, it was used the methodology of Textual Analysis Discourse, recommended by Moraes and Galiazzi (2006), due to consider it as the most appropriate to study the phenomenon investigated here. 98 surveys were analyzed (Msd dissertations and PhD thesis). The results were organized into categories, according to the curriculum development levels, described by Sacristan (2000). Relating to prescribed curriculum, the articles analyzed show teachers the references on how to plan teaching practice, which in the process until reach the classroom, pass through the curriculum presented to teachers as books and textbooks that allows them (for being more in touch with these materials) to organize their planning. As a result referring to curriculum modeled by teachers, we can stand out important issues such as multiculturalism, ethnomathematics, cultural diversity, among others that enable the achievement of the curriculum in action and accomplished, which verifies if there was effectively learning and to what extent there is a coherence in the process from the prescribed curriculum to the accomplished curriculum. Finally, the evaluated curriculum points out that the external and internal evaluations end up inducing the curriculum that are practiced in class situations